Early Somatosensory Processing Over Time in Individuals at Risk to Develop Psychosis - Hagenmuller, Florence; Heekeren, Karsten; Roser, Patrik; Haker, Helene; Theodoridou, Anastasia; Walitza, Susanne; Rössler, Wulf; Kawohl, Wolfram (Frontiers in Psychiatry, 2019)
Objective: Somatosensory evoked potentials (SEPs) enable the investigation of thalamocortical and early cortical processing. Previous studies reported alterations of SEPs in patients with schizophrenia as well as in individuals in the prodromal stage. Moreover, cannabis use as an environmental risk factor for the development of schizophrenia has been demonstrated to influence SEP parameters in individuals at risk to develop psychosis. SEPs show high-frequency (HFOs) oscillations superimposed on the primary cortical response (N20). The aim of this study was to explore the course of SEP changes and the impact of concomitant cannabis use in individuals at risk to develop psychosis who sought medical help. Methods: Median nerve SEPs including high-frequency oscillations (HFOs) superimposed on the primary cortical response (N20) were investigated using multichannel EEG in individuals (n=54 at baseline) remaining at risk to develop psychosis at follow-up after one year (high-risk: n=19; ultra-high-risk: n=27) versus subjects with conversion to psychosis (n=8) and a healthy control group (n=35). Longitudinal and cross-sectional analyses of SEP components as estimated by dipole source analysis were performed. Results: The longitudinal development of the N20 strength depended on cannabis use. In cannabis non-users, a greater decrease of N20 strengths over time was associated with more negative symptoms at baseline. At baseline, converters did not differ from subjects remaining at risk. At follow-up, converters showed increased low- and high-frequency activity than at-risk subjects and did not differ from controls. Conclusion: The results of this study lead to the suggestion that these deficits in early somatosensory processing in individuals at risk to develop psychosis may not represent a marker for a genetic risk for psychosis but rather reflect state-dependent factors such as negative symptoms. On the other hand, theA transition to psychosis may seems to represent an interstage between reduced sensory registration from the at-risk state and gating deficits in the chronic state.